Soluble immune checkpoint factors reveal high-risk osteosarcoma subtypes and enable early metastasis prediction - Peng, Hanqi; Li, Binghao; Cui, Jiameng; Sun, Gege; Wang, Qinchuan; Zhu, Yun; Wang, Sicong; Tu, Huakang; Wu, Xifeng; Ye, Zhaoming (Frontiers in Immunology, 2025)
BackgroundOsteosarcoma is a rare disease, yet it is the most frequent primary malignant bone tumor, with poor survival in metastatic cases. Current PD-1 and PD-L1 checkpoint inhibitors show limited efficacy in osteosarcoma, necessitating further investigation into other immune checkpoint factors.MethodsWe analyzed immune checkpoint proteins in plasma from 67 osteosarcoma patients and 50 healthy controls, examined their transcriptional levels in tumor tissues, validated the results using public databases, and elucidated potential mechanisms.ResultsCD48, TIMD-4, B7-H6, CD134, B7-H5, CD47, and S100A8/A9 were significantly elevated in osteosarcoma patients, each linked to increased osteosarcoma risk. In patients who developed metastasis, CD48, B7-H2, TIMD-4, B7-H6, CD134, B7-H5, CD47, and S100A8/A9 were also elevated and correlated with higher metastasis risk. Using peripheral blood levels of these eight factors, we identified osteosarcoma immune subtypes and built an excellent predictive model for metastasis (C-index = 0.876, predicting metastasis within one year). The gene expression of these factors in tumor tissues showed an inverse correlation with metastasis compared to peripheral blood. Single-cell analysis revealed differential expression of these factors in non-specific immune cells from metastatic patients.ConclusionSoluble immune checkpoint factors were identified as significantly associated with osteosarcoma metastasis. Using peripheral blood biomarkers, we characterized immune subtypes of osteosarcoma, and developed a predictive model for metastasis. These biomarkers may serve as potential therapeutic targets for future immunotherapy.